Analisis Kendala Manajemen Pengelolaan Bauran Pemasaran (Product, Price, Place, Dan Promotion) UPTD. Museum Bali - Isaura, Isaura; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 12 No 1 (2024): VOL 12, NO 1 (2024): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2024)
Tourist visits to the Bali Museum have exhibited significant inconsistency from 2014 to 2023. However, from 2002 to 2014, tourist visits at the Bali Museum increased, due to implementation of the 4P marketing mix. This study aims to analyze the obstacles faced by the UPTD. Museum Bali management in implementing the 4P marketing mix promotion in the present context. This study is qualitative research, drawing primary data from documentation, interviews, and observation. The data analysis technique used in this study is descriptive qualitative, including data reduction, triangulation, and drawing conclusions. The results of this study show that the obstacles UPTD. Museum Bali faces in implementing the 4P marketing mix are due to the top-down approach. Consequently, UPTD. Museum Bali lacks authority in the planning, organizing, actuating, and controlling aspects of the 4P marketing mix (product, price, place, and promotion), as well as insufficient budget allocation to develop it. As a result, these obstacles affect tourist visits. It is recommended that the government adopt a combination of top-down and bottom-up approaches to build strategic relationships to overcome the challenges and increase tourist visits at the Bali Museum. Keywords: Marketing Mix, Obstacles, Top-down.